Epictia albipuncta BURMEISTER, 1861 (SERPENTES: LEPTOTYPHLOPIDAE) FIRST RECORD FOR THE FORMOSA PROVINCE, ARGENTINA - Ruiz García, José Augusto; Tedesco, María Esther; Stechina, Ornela Sofía; Céspedez, Jorge Abel (Boletín de la Sociedad Zoológica del Uruguay, 2020)
Epictia albipuncta Burmeister, 1861 is a small-sized snake distributed in Argentina, Brasil, Bolivia, Paraguay and Perú. In this study, we report a first record of E. albipuncta from Formosa province in the wet eastern district. Our record extends the geographic distribution in 193 km northeast from the nearest previously known locality Presidencia Roque Sáenz Peña, Chaco province.